Triple Bottom Model Towards Sustainability Report - Putra, Adrie; Suliati, Retna; Rudianto; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to provide empirically the effect between the applications of the Elkington triple bottom line concept on the sustainability report. The analysis in this study uses the independent variable Profit with a Return on Asset (ROA) proxy, People with an Intellectual Capital (IC) proxy and Planet with a Corporate Social Responsibility (CSRi) proxy index. The sample used in this study is public traded companies (Tbk) incorporated in the mining industry. This research uses sampling with purposive sampling method. Collecting data with literature studies, where 145 samples were collected by companies. The data analysis method used in this study uses multiple regression analysis, by testing the F test and t test hypotheses. The results of this study indicate that the concept of a triple bottom line has not fully influenced the sustainability report in accordance with the concept put forward by Elkington, the results of research in a research model can be accepted, while the partial profit and people test shows a significant influence on sustainability report reporting, while the planet does not significantly influence the sustainability report.